PELATIHAN PEMBUATAN BATIK ECOPRINT SEBAGAI PENINGKATAN KREATIVITAS ANAK DI KINDERHUT INDONESIA - Rachmadani, Nisa Putri; Kafri, Saniman Andi; Wijaya, Reza Sastra (Jurnal Abdi Insani, 2025)
Kinderhut Indonesia is a social welfare development institution that was established in February 2005, precisely after the earthquake and tsunami tragedy that hit Aceh. The Kinderhut Indonesia Foundation has a mission to improve the welfare of orphans, and underprivileged and neglected children by ensuring that they get their rights, especially in terms of education, both through formal and non-formal education. This community service activity aims to improve the creativity and skills of the foundation's foster children in the arts, as well as foster an entrepreneurial spirit. This training uses the ecoprint method, which is a natural fabric dyeing technique, which is in line with the concept of sustainability and supports the sustainable development goals (SDGs). The methods used are participatory and applicative, consisting of: preparation, implementation, and evaluation. The preparation stage includes planning, scheduling, and procurement of tools and materials. The implementation stage consists of material socialization, ecoprint pattern design, ecoprint practice (steam technique), and final product development. Evaluation is carried out using the pretest-posttest method to measure the improvement of participants' skills. The results of the ecoprint batik training at the Kinderhut Indonesia Foundation showed an increase in the creativity and skills of the foster children in creating environmentally friendly products that have a selling value. During eight meetings, participants were trained to produce various ecoprint batik which were transformed into products such as bags, clothes, tablecloths and pillowcases. The evaluation showed a success rate of 73%, based on aspects of neatness, smoothness, and technical accuracy. This activity also fosters an entrepreneurial spirit and supports sustainable development. However, time constraints are an obstacle in the distribution of participants' understanding. This program is expected to be the basis for the development of sustainable skills and entrepreneurial potential for the foundation and its foster children in the future.